Stevens-Johnson Syndrome in Adult Patient Secondary to COVID-19 Infection: Case Report - Pandharinath Khade; Avani Shah; Vidya Kharkar (JMIR Dermatology, 2023)
COVID-19 is a global pandemic caused by a novel zoonotic RNA virus named SARS-CoV-2. Various cutaneous manifestations associated with COVID-19 have been described, including urticarial rash, confluent erythematous rash, papulovesicular exanthem, chilblain-like acral pattern, livedo reticularis, and purpuric vasculitis pattern. Here, we are presenting a case of a 45-year-old male with mucocutaneous features of Stevens-Johnson syndrome.